An Economic Analysis on the Transition to Dryland Production in Deficit-Irrigated Cropping Systems of the Texas High Plains - Mitchell-McCallister, Donna; McCullough, Rebecca; Johnson, Phillip; Williams, Ryan Blake (Frontiers in Sustainable Food Systems, 2021)
The objective of this analysis was to successfully integrate hydrologic, agronomic, and economic methods to evaluate various management strategies by changing crop choices to better manage the dwindling resources of the Ogallala aquifer. A non-linear optimization model was used to estimate the optimal water use, crop mix, crop yield, and net returns over a 50 year period under dryland and deficit irrigation scenarios in the Texas High Plains. Results indicate growers can maintain profitability by switching from fully irrigated center pivots to irrigating ½ and ¼ pivots.